Explaining the Structural Model of Marital Satisfaction Based on Spirituality with the Mediating Role of Happiness in Married Women - Zarei, Maede; Zhian Bagheri, Masoumeh; Belyad, MohammadReza; Ranjbaripour, Tahereh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to explain the structural model of marital satisfaction based on spirituality with the mediating role of happiness in married women.Methods: The research method was descriptive-correlational of the structural equation modeling (SEM) type. The statistical population included all married women employed in schools in Tehran. The total number was 41,656 in the 2022–2023 academic year. The sample size was calculated based on the PLS method proposed by Barclay et al. (1995), which required a minimum of 70 participants. However, due to the potential risk of participant attrition, a larger sample of approximately 120 individuals was examined. The sampling method used in this study was convenience sampling. The measurement instruments included the Enrich Marital Satisfaction Questionnaire (1989), the Parsian and Dunning Spirituality Questionnaire (2009), and the Oxford Happiness Questionnaire (1989). The assumptions were analyzed using SPSS 26 and SMART-PLS statistical software.Findings: The results of this study indicated that the structural model of marital satisfaction based on spirituality, with happiness as a mediator, demonstrated a good and acceptable fit, with a significance level of 0.05. Therefore, it is predicted that the structural model of marital satisfaction based on spirituality with the mediating role of happiness applies to married women. Consequently, spirituality, mediated by happiness, enhances marital satisfaction.Conclusion: Thus, by increasing the level of spirituality among couples, with happiness as a mediator, a higher level of marital satisfaction can be anticipated.